Current concepts about treatment options of plantar fibromatosis: A systematic review of the literature. Issue 5 (October 2019) - Fuiano, Mario; Mosca, Massimiliano; Caravelli, Silvio; Massimi, Simone; Benedetti, Maria Grazia; Di Caprio, Francesco; Mosca, Salvatore; Zaffagnini, Stefano
Highlights: Plantar fibromatosis (or Ledderhose's disease) is a benign condition, but characterized by local aggressiveness and high recurrence rate. Plantar fibromatosis often tends to recur after operative removal. A complete excision of the lesion without leaving pathological tissue is necessary to minimize the risk of recurrence. Conservative treatment should always be the first approach. Local or marginal excision are not recommended in the treatment of this disease, both in primary than in recurrence cases. An exception could be lesions still very small and locally not aggressive, in patients with a low risk of recurrence. Abstract: Background: Plantar fibromatosis, or Ledderhose disease, is a benign and hyperproliferative disease of the plantar aponeurosis. There have been described different therapeutic options regarding plantar fibromatosis, both conservative and surgical. The aim of this review is to systematically analyze conservative and operative treatments of plantar fibromatosis described in literature, evaluating which procedure shows the highest success rate and best functional outcome. Methods: A systematic review of PubMed, Google Scholar and Cochrane reviews computerized database was performed focusing on the different types of treatments for plantar fibromatosis. Research was performed using the keywords "plantar", "fibromatosis", "Ledderhose", "Dupuytren", "foot" in order to identify all papers regarding the treatment of plantar fibromatosis. In addition, the research was extended to the reference list of the relevant articles. A total of 25 citations were obtained from the research and included. Results: Considering all the studies, 233 patients were included in this systematic review. 5 studies reported conservative treatment of plantar fibromatosis, with a total of 35 patients included. Operative outcomes are reported for 178 patients (92 male, 86 female), with 196 feet treated. Conclusions: Valid conservative methods are presented in literature, with debated results. Some operative options show high recurrence rate; wide excision is recommended in selected cases. Further clinical trials with well-defined and standardized outcome measurements should be necessary in future to better evaluate success rate and complications of the various procedures.